2021
DOI: 10.1186/s40748-021-00134-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of neonatal hypothermia among very low birth weight infants: a Meta-analysis

Abstract: Background Neonatal admission hypothermia (HT) is a frequently encountered problem in neonatal intensive care units (NICUs) and it has been linked to a higher risk of mortality and morbidity. However, there is a disparity in data in the existing literature regarding the prevalence and outcomes associated with HT in very low birth weight (VLBW) infants. This review aimed to provide further summary and analyses of the association between HT and adverse clinical outcomes in VLBW infants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…While hypothermia has been associated with high rates of mortality in the adult and neonatal intensive care unit literature, the prevalence and prognosis for previously healthy infants with hypothermia has yet to be quantified 17–24 . Therefore, guidelines regarding the management of hypothermic infants presenting to the ED are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While hypothermia has been associated with high rates of mortality in the adult and neonatal intensive care unit literature, the prevalence and prognosis for previously healthy infants with hypothermia has yet to be quantified 17–24 . Therefore, guidelines regarding the management of hypothermic infants presenting to the ED are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…mia has yet to be quantified. [17][18][19][20][21][22][23][24] Therefore, guidelines regarding the management of hypothermic infants presenting to the ED are lacking. | 43…”
Section: Discussionmentioning
confidence: 99%
“…This statistically significant association between thrombocytopenia and hospital mortality reaffirms the importance of early diagnosis and management of thrombocytopenia in determining neonatal outcomes. Thrombocytopenia is mostly common in hypothermic preterm babies because of the increased risk of sepsis, necrotizing enterocolitis, and slowing down of coagulation enzymes, disordered fibrinolysis, and disruption of platelet function [ 4 , 19 , 24 ]. Moreover, in our setting, management of thrombocytopenic preterm infants is still deficient (gap in accessibility, appropriate storage, and proper administration of blood components), contributing to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Basic information, neonatal characteristics, newborn care-related factors, general medical condition, and the mother's delivery summary were all retrieved and collected from hospital records of preterm babies. The data extraction form was prepared based on the Federal Ministry of Health NICU management protocol [ 3 ], thermal protection WHO practical guide [ 4 ], and other peer-reviewed articles [ 8 , 12 , 19 21 ]. Five BSc (Bachelor of Science) neonatal nurses and two MSc (Masters of Science) holders were recruited for data collection and supervision, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature is an outcome that increases the risk of morbidity and mortality in this population. Mohamed et al [ 9 ] found the hypothermia is associated with mortality (OR = 1.89; 1.72–2.09), intra-ventricular hemorrhage (OR = 1.86; 1.09–3.14), bronchopulmonary dysplasia (OR = 1.28; 1.16–1.40) or neonatal sepsis (OR = 1.47; 1.09–2.49), and retinopathy of prematurity (OR = 1.45; 1.28–1.72). Similar results were found in other studies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%